Effect Of The Stopping Stripping Production Line To OEE (Overall Equipment Effectiveness) Of The Stripping Machine On The Primary Packaging Processes In The Pharmaceutical Industry - Kelvin Fernando Pratama; Anis Yohana Chaerunisaa (Indonesian Journal of Pharmaceutics, 2022)
Increased production output is the main priority in the pharmaceutical industry. Productivity of primary packaging process which plays an important role in producing output can be improved and maintained by conducting regular OEE (Overall Equipment Effectiveness) analysis of the machinery and processes. OEE is a calculation method that is carried out thoroughly to identify the level of productivity and performance of machines or equipment. The OEE consists of three main measurements, namely availability, performance, and quality. In this study, line stop activities were observed during the primary packaging process that affected the OEE value of stripping machines in one of the pharmaceutical industries in the city of Jakarta. Research is carried out by observing, recording, and processing data related to primary packaging processes such as line stops and the number of products produced. Based on our study, we found that most of the line stops in the primary packaging process are caused by the changing of the polycellonium of the primary packaging material. Thus, we conclude that reducing changing of the polycellonium time from 10 minutes to 5 minutes will be beneficial to increase the operating time by 8% and increase the OEE value by 5%.Keywords: Primary Packaging Process, Overall Equipment Effectiveness (OEE),  Stripping Machine, Net Operating Time